Cross-cultural adaptation, reliability and validity of the Fremantle Knee Awareness Questionnaire in Italian subjects with painful knee osteoarthritis - Monticone, Marco (Health Qual Life Outcomes, 2021)
BACKGROUND AND AIM: Growing attention is being given to utilising physical function measures to better understand and manage knee osteoarthritis (OA). The Fremantle Knee Awareness Questionnaire (FreKAQ), a self-reported measure of body-perception specific to the knee, has never been validated in Italian patients. The aims of this study were to culturally adapt and validate the Italian version of the FreKAQ (FreKAQ-I), to allow for its use with Italian-speaking patients with painful knee OA. METHODS: The FreKAQ-I was developed by means of forward–backward translation, a final review by an expert committee and a test of the pre-final version to evaluate its comprehensibility. The psychometric testing included: internal structural validity by Rasch analysis; construct validity by assessing hypotheses of FreKAQ correlations with the knee injury and osteoarthritis outcome score (KOOS), a pain intensity numerical rating scale (PI-NRS), the pain catastrophising scale (PCS), and the Hospital anxiety and depression score (HADS) (Pearson’s correlations); known-group validity by evaluating the ability of FreKAQ scores to discriminate between two groups of participants with different clinical profiles (Mann–Whitney U test); reliability by internal consistency (Cronbach’s alpha) and test–retest reliability (intraclass correlation coefficient, ICC(2.1)); and measurement error by calculating the minimum detectable change (MDC). RESULTS: It took one month to develop a consensus-based version of the FreKAQ-I. The questionnaire was administered to 102 subjects with painful knee OA and was well accepted. Internal structural validity confirmed the substantial unidimensionality of the FreKAQ-I: variance explained was 53.3%, the unexplained variance in the first contrast showed an eigenvalue of 1.8, and no local dependence was detected. Construct validity was good as all of the hypotheses were met; correlations: KOOS (rho = 0.38–0.51), PI-NRS (rho = 0.35–0.37), PCS (rho = 0.47) and HADS (Anxiety rho = 0.36; Depression rho = 0.43). Regarding known-groups validity, FreKAQ scores were significantly different between groups of participants demonstrating high and low levels of pain intensity, pain catastrophising, anxiety, depression and the four KOOS subscales (p ≤ 0.004). Internal consistency was acceptable (α = 0.74) and test–retest reliability was excellent (ICC = 0.92, CI 0.87–0.94). The MDC(95) was 5.22 scale points. CONCLUSION: The FreKAQ-I is unidimensional, reliable and valid in Italian patients with painful knee OA. Its use is recommended for clinical and research purposes. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12955-021-01754-4.